Genetic diversity and response of gladiolus (Gladiolus hybridus) hybrids for growth, flowering and corms traits under ecological conditions of Delhi - SWAROOP, KISHAN; SINGH, KANWAR PAL; KUMAR, PRABHAT; JANAKIRAM, T (The Indian Journal of Agricultural Sciences, 2016)
The experiment was conducted with 22 hybrids and one check of Gladiolus hybridus at the research farm of the Division of Floriculture and Landscaping, Indian Agricultural Research Institute, New Delhi for three years from 2012-13 to 2014-15 to study their performance and genetic diversity under ecological conditions of Delhi for commercial traits. The mean performance (3 years) of gladiolus hybrids in terms of all vegetative and flower characters studied revealed and produced maximum plant height (133.33 cm), spike length (112.22 cm), diameter of flower (11.18 cm), width of tepal (5.33 cm), number of corms (3.55) and cormels/plant (85.11) by Pink Parassol Open seedling hybrid. Two hybrids namely P-16-1 × Eurovision and Melody Open seedling were found to be earliest and flowered in 75.44 and 75.66 days, respectively. One hybrid, i.e. AVE × Mayur had produced more number of florets/spike (21.10). Maximum length of tepal (7.41 cm), length of leaf (46.55 cm), width of leaf (3.94 cm), number of leaves/plant (7.22) were recorded in Melody Open seedling, P-16-1 × Eurovision, Salmon Queen Open seedling, Melody × Bindiya hybrids, respectively.